Legal Regulation of The Debtor’s Obligation To Submit An Insolvency Application: Comparative Study Between Jordanian and French Legislations - Ismaeel Nayef Alhadidi; Mohammad Ahmad Rahamneh (Journal of Legal Sciences, 2024)
This research addressed the issue of the legal obligation imposed on the debtor to submit legal action to declare his insolvency when its conditions are met in accordance with Jordanian legislation, as well as the sanction resulting from the debtor’s failure to carry out this obligation in accordance with the same legislation. The study included multiple problems raised by the legal regulation of the application for declaration of insolvency and the sanction resulting from the non-observation of such an obligation. The most important of these problems are the legal regulation of the necessary conditions for submitting the application within a certain period, the legal characterization of that period, the authority of the court to impose the sanction resulting from failure to comply with the obligation, and the extent of its susceptibility to appeal. To address the problem of the study, a descriptive analytical approach was followed, while resorting to the topical comparative approach. In fact, the relevant legal texts were analyzed and topical comparison was conducted – when needed - with French legislation. The study reached several results, the most important of which are that the debtor is not exempted from his obligation to submit an application for the seek of insolvency declaration, even if this application is submitted by one of the creditors or the general controller of companies, as long as its conditions are met, and the possibility of appealing the decision issued by the court to impose a sanction on the debtor for not submitting an insolvency declaration application, which takes place when appealing the court’s decision issued regarding the insolvency declaration application. The study also came up with several recommendations, the most important of which are: it is necessary to stipulate explicitly that the debtor is not required to submit an application for declaration of imminent insolvency, and it is necessary to state explicitly that submitting an application for declaration of actual insolvency without its legally required attachments or failure to complete those attachments within the specified period of time does not make the debtor immune from the imposition of the legal sanction provided for not submitting an insolvency declaration application.